"Becoming" an environmentalist in Indonesia. (June 2015) - Nilan, Pam; Wibawanto, Gregorious Ragil
Highlights: Examines how new grassroots environmental groups emerge in Indonesia. Uses the work of Delueze and Guattari: Becoming, assemblage and the rhizome. Becoming-environmentalist means separation from the mainstream into new territory. Uncovers complex new ground; decentred, diverse local urban environmental activism. Abstract: This article looks at how five environmental leaders in Jogjakarta became environmentally active, and at the groups and interventions they formed. Interview data are drawn from a broader project that aimed to find out what might turn an Indonesian person into someone who cares for the environment. It examines the journey in leadership as "becoming" in the terms of Deleuze and Guattari (1987); a journey constituted in the desire to make something different. Against a backdrop of day-today practices in Central Java that do not favour environmental conservation and sustainability, the five informants seized upon an idea, a praxis, and explored it in the company of like-minded others, to join or make an organisation or action dedicated to redressing environmental crisis or neglect.